2018
DOI: 10.1111/jonm.12681
|View full text |Cite
|
Sign up to set email alerts
|

Supervisory relationships in long-term care facilities: A comparative case study of two facilities using complexity science

Abstract: Nurse managers who provide effective supervisory support can improve the quality of care provided to their residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 33 publications
3
29
0
4
Order By: Relevance
“…There should be an acknowledgement that a certain level of experience is required to meet the demands placed upon charge nurses by the multiple dimensions and responsibilities of this role. We may be setting charge nurses up for failure and jeopardising their health by recruiting new graduates for this role, which may lead to deleterious effects on resident outcomes (Prentice et al, ), the work environment and staff outcomes (Escrig‐Pinol et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There should be an acknowledgement that a certain level of experience is required to meet the demands placed upon charge nurses by the multiple dimensions and responsibilities of this role. We may be setting charge nurses up for failure and jeopardising their health by recruiting new graduates for this role, which may lead to deleterious effects on resident outcomes (Prentice et al, ), the work environment and staff outcomes (Escrig‐Pinol et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…All project data were collected in 2015, including the subset of data used for this study (i.e., interviews with RNs). Further details on the project's background and methodology are included in recent publications (Escrig‐Pinol, Corazzini, Blodgett, Chu, & McGilton, ; Prentice et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Supervisors need to focus on supporting their staff, and provide opportunities to build knowledge and skills to address and reduce resident's responsive behaviours. These actions would influence nursing homes staffs' satisfaction with work, and ultimately their retention (Chu et al, 2016;Escrig-Pinol et al, 2019;Bethell et al, 2018).…”
Section: Impli C Ati On S For N Ur S Ing Manag Ementmentioning
confidence: 99%
“…In summary, previous research has identified that supervisory support, work effectiveness and work empowerment have been positively associated with job satisfaction of nurses and NAs (Aloisio et al., 2019; Chamberlain et al., 2016; Li et al., 2013; Schwendimann et al., 2016; Squires et al., 2015). It has also been suggested that supervisors have a key role in addressing stressful resident issues of their staff and that positive work environments and effective collaboration among team members have positive outcomes (Escrig‐Pinol et al., 2019). Examples of this include the following: lower risk of staff assault (Isaksson, 2013; Sharipova et al., 2010), and reduced staff stress linked to residents with responsive behaviours by fostering staff to work together to be responsive to resident needs, and for supervisors to pitch in to support staff when required (Escrig‐Pinol et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…With the aging of global population, the needs for long-term care (LTC) have increased signi cantly. However, most of long-term care facilities (LTCFs) have been faced with the sta ng challenges, resulting in poor capacity to provide competent and high-quality long-term care to the elderly [1][2][3]. Health care aides (HCAs, equivalent to nursing assistants) provided 80%~90% of the direct care to LTCF residents [4].…”
Section: Introductionmentioning
confidence: 99%